Clinical, laboratory, and therapeutic characteristics of American tegumentary leishmaniasis in the 15 th State Health Division, Northwest Paraná State, Southern Brazil - Nassif,Priscila Wolf (2016)
Abstract INTRODUCTION American tegumentary leishmaniasis (ATL) is an endemic disease in many regions of Brazil; however, only few reports on the actual epidemiological conditions are available. Here, we aimed to assess the clinical, epidemiological, and laboratory characteristics of ATL patients and their treatment in the 15th Regional Health Division of Paraná State, Maringá, Brazil. METHODS This epidemiological study included patients diagnosed with ATL from January 2010 to September 2014, from the 15th Regional Health Division database. RESULTS A total of 220 cases aged 3-84 years (85% male and 60.9% with up to 8 years of schooling) were included. The cases were classified as having the cutaneous form (n=183; 83.2%), mucosal form (n=26; 11.8%), mucocutaneous form (n=11; 5%), and relapses (n=21; 9.6%). Diagnosis was made via laboratory test results in 197 (89.5%) patients, and 172 (78.2%) completed the treatment within the study period. With regard to patients with the cutaneous form, 134 (95%) were cured, 131 (97.8%) were treated with Glucantime(r), and 47 (36.7%) received dosage of >15 and <20mg Sb5+/kg/day. Among the cases with mucosal involvement, 87.1% were cured and most were treated with <20mg Sb5+/kg/day. Thus, the cure rate was 93.6%. CONCLUSIONS During the study period in the 15th Regional Health Division of Paraná State, ATL cases had a good response to treatment with a low rate of relapse or treatment failure, although a high percentage of mucosal or mucocutaneous form cases was also noted.